Representations of task assignments in distributed systems using Young tableaux and symmetric groups. Issue 2 (3rd March 2016) - Kim, Dohan
Abstract : This article presents a novel approach to representing task assignments for partitioned agents (respectively, tasks) in distributed systems. A partition of agents (respectively, tasks) is represented by a Young tableau, which is one of the main tools in studying symmetric groups and combinatorics. In this article, we propose a task, agent and assignment tableau in order to represent a task assignment for partitioned agents (respectively, tasks) in a distributed system. This article is concerned with representations of task assignments rather than finding approximate or near optimal solutions for task assignments. A Young tableau approach allows us to raise the expressiveness of partitioned agents (respectively, tasks) and their task assignments.